Peasant economics farm households and agrarian developoment. - Ellis, Frank, 1947- (Cambridge ; New York, NY, USA Cambridge University Press, 1988)
A textbook on the economics of farm households in developing countries
Php 350.00
Includes bibliographical references (pages 286-298) and indexes.
Donated by Dr. Ma. Luisa Mabunay (VML011651g)
Keywords: Peasants -- Developing countries -- Economic conditions; Peasants -- Developing countries -- Social conditions; Quality of life -- Developing countries; Developing countries -- Rural conditions